Monoclonal Antibody-Glial-Derived Neurotrophic Factor Fusion Protein Penetrates the Blood-Brain Barrier in the Mouse - Zhou, Qing-Hui (The American Society for Pharmacology and Experimental Therapeutics, 2010)
Glial-derived neurotrophic factor (GDNF) is a potent neuroprotective agent for multiple brain disorders, including Parkinson's disease. However, GDNF drug development is difficult because GDNF does not cross the blood-brain barrier (BBB). To enable future drug development of GDNF in mouse models, the neurotrophin was re-engineered as an IgG fusion protein to enable penetration through the BBB after intravenous administration. The 134-amino acid GDNF was fused to the heavy chain of a chimeric monoclonal antibody (MAb) against the mouse transferrin receptor (TfR) designated the cTfRMAb. This antibody undergoes receptor-mediated transport across the BBB and acts as a molecular Trojan horse to ferry the GDNF into mouse brain. The cTfRMAb-GDNF fusion protein was expressed by stably transfected Chinese hamster ovary cells, affinity-purified, and the biochemical identity was confirmed by mouse IgG and GDNF Western blotting. The cTfRMAb-GDNF fusion protein was bifunctional and bound with high affinity to both the GDNF receptor α1, ED(50) = 1.7 ± 0.2 nM, and the mouse TfR, ED(50) = 3.2 ± 0.3 nM. The cTfRMAb-GDNF fusion protein was rapidly taken up by brain, and the brain uptake was 3.1 ± 0.2% injected dose/g brain at 60 min after intravenous injection of a 1-mg/kg dose of the fusion protein. Brain capillary depletion analysis showed the majority of the fusion protein was transcytosed across the BBB with penetration into brain parenchyma. The brain uptake results indicate it is possible to achieve therapeutic elevations of GDNF in mouse brain with intravenous administration of the cTfRMAb-GDNF fusion protein.